Fundamentals of translation - Colina, Sonia (Cambridge University, 2015)
Includes bibliographical references (pages 301-304) and index; "This textbook provides a non- technical introduction to the basic and central concepts of translation theory and practice, including translation briefs, parallel texts and textual functions, cohesion and coherence, and old and new information"-- Provided by publisher